Prevention of Radicalism and Terrorism in Higher Education: Regulation and Implementation - Saman, Moh; Aflah, Muhammad Hilmi Naufal; Febriyanti, Diyah Anggun; Afifah, Bayyinatun; Masyhar, Ali; Arifin, Ridwan (Indonesian Journal of Advocacy and Legal Services, 2023)
The emergence of various cases of radicalism in universities is the responsibility of all parties. Various cases that occur in universities show that campuses in Indonesia are very vulnerable to being compiled by radical ideas and terrorism movements, even considered to have no clear curriculum direction in preventing radicalism and terrorism. This study aims to analyze three important things in the issue of radicalism and terrorism in universities, especially at Semarang State University, namely, first how radicalism prevention policies in universities (study at UNNES); second, how to implement policies to prevent radicalism and terrorism at UNNES; and third, how UNNES campus efforts to overcome students or lecturers exposed to radicalism and terrorism. The method used in this study is a mixed method that combines normative juridical research with empirical data in the field. The projected results of this study are in the form of real data regarding the implementation of religious freedom regulations on the UNNES campus. The output of this research is in the form of articles published in accredited national journals.